The Phenomenon of Emerging Addictions: A Critical Review of Selected Behavioral Disorders of Significant Social Concern (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This critical review examines emerging behavioural addictions, focusing on gambling disorder, Internet addiction (including gaming disorder), cybersex and love addiction. Although not substance-related, they share psychopathological and neurobiological mechanisms with traditional addictions, requiring a multidimensional diagnostic and rehabilitative approach. It highlights the importance of functional diagnosis, holistic assessment and evidence-based psychosocial treatments (CBT, DBT). Comorbidity with personality disorders, particularly dependent personality disorder, is discussed, as well as the relevance of a recovery-oriented approach and neuroplasticity. It concludes by emphasising the need for further research and greater integration into diagnostic systems to improve clinical management.
Keywords: behavioural addictions; gambling disorder; cybersex addiction; love addiction; dual diagnosis